Histological changes in the hippocampus of both cerebral hemispheres of Wistar and SHR rats under experimental chronic cerebral hypoperfusion - O. Yu. Harmatina; K. V. Rozova; А. H. Portnychenko (Patologìâ)
Сhronic cerebral hypoperfusion (ChCH) and arterial hypertension are the factors of risk for сerebrovascular diseases, nevertheless the underlying pathophysiological mechanisms remain unclear.